Michelson interferometer with porch swing bearing for portable FTIR spectrometer - Välikylä, Tuomas (fi=Turun yliopisto|en=University of Turku|, 2014)
The interferometer for low resolution portable Fourier Transform middle infrared spectrometer was developed and studied experimentally. The final aim was a concept for a commercial prototype. Because of the portability, the interferometer should be compact sized and insensitive to the external temperature variations and mechanical vibrations. To minimise the size and manufacturing costs, Michelson interferometer based on plane mirrors and porch swing bearing was selected and no dynamic alignment system was applied. The driving motor was a linear voice coil actuator to avoid mechanical contact of the moving parts. The driving capability for low mirror driving velocities required by the photoacoustic detectors was studied. In total, four versions of such an interferometer were built and experimentally studied. The thermal stability during the external temperature variations and the alignment stability over the mirror travel were measured using the modulation depth of the wide diameter laser beam. Method for estimating the mirror tilt angle from the modulation depth was developed to take account the effect from the non-uniform intensity distribution of the laser beam. The spectrometer stability was finally studied also using the infrared radiation. The latest interferometer was assembled for the middle infrared spectrometer with spectral range from 750 cm−1 to 4500 cm−1. The interferometer size was (197 × 95 × 79) mm3 with the beam diameter of 25 mm. The alignment stability as the change of the tilt angle over the mirror travel of 3 mm was 5 μrad, which decreases the modulation depth only about 0.7 percent in infrared at 3000 cm−1. During the temperature raise, the modulation depth at 3000 cm−1 changed about 1 . . . 2 percentage units per Celsius over short term and even less than 0.2 percentage units per Celsius over the total temperature raise of 30 °C. The unapodised spectral resolution was 4 cm−1 limited by the aperture size. The best achieved signal to noise ratio was about 38 000:1 with commercially available DLaTGS detector. Although the vibration sensitivity requires still improving, the interferometer performed, as a whole, very well and could be further developed to conform all the requirements of the portable and stable spectrometer.